História do turismo em Petrópolis entre 1900 e 1930 - Daibert, André Barcelos Damasceno (2010)
The present paper intended to analyze the way the construction of the so called 'touristic nature' of the town of Petrópolis was originated, through a historical perspective. As an specific object, I intended to describe how the organization of the touristic activity in the town happened., highlighting its origins, trying to comprehend and identify the main narratives and images in which the cultural construction relies on, highlighting its origins between the years of 1900 and 1930. With this aim, the paper put forward the origins and evolution of the town of Petrópolis since the antecedents of its foundation in the 19th century. Following it, I worked in the sense of unveil the social changes in the act of travelling, in the perspective of comprehending the origins and consolidation of the organized touristic activity in town. Finally, I analyzed some narratives and images which represent the cultural construction of the 'touristic nature' of Petrópolis, holding as reference the first decades of the 20th century. The study was done with the resource of the existing techno-scientific literature and, also the documentary and iconographic research which portrayed narratives and images of tourism in Petrópolis at the beginning of its organization. Therefore, guides and magazines published between the years of 1900 and 1930 were selected.